Fever of unknown origin − diagnostic methods in a European developing country - Bosilkovski, Mile; Dimzova, Marija; Stevanović, Milena; Semenakova Cvetkovska, Vesna; Vasileva Duganovska, Maja (Vojnosanitetski pregled, 2017)
Background/Aim. Fewer of unknown origin (FUO) remains amongst the most difficult diagnostic dilemmas in contemporary medicine. The aim of this study was to determine the causes of FUO and to identify the methods of diagnosis in patients with FUO in a tertiary care setting in the Republic of Macedonia. Methods. Retrospectively histories of 123 immunocompetent patients older than 14 years with classical FUO that had been examined at the University Hospital for Infectious Diseases and Febrile Conditions in the city of Skopje, during the period 2006−2012 were evaluated. FUO was defined as axillary fever of ≥ 37.5°C on several occasions, fever duration of more than 21 days and failure to reach the diagnosis after the initial diagnostic workup comprised of several defined basic investigations. Results. Infections were the cause of FUO in 51 (41.5%) of the patients, followed by non-infective inflammatory disorders (NIID) in 28 (22.8%), miscellaneous in 12 (9.7%) and neoplasm in 11 (8.9%) of the patients. Twenty one of the patients (17.1%) remained undiagnosed. The most common causes for FUO were visceral leishmaniasis, abscesses, urinary tract infections, subacute endocarditis, polymyalgia rheumatica and adult onset of Still disease. The final diagnosis was reached with histology in 24 (23.5%), imaging and endoscopic procedures in 21 (20.6%), clinical course and empiric therapy response in 20 (19.6%), serology in 18 (17.6%) and cultures in 16 (15.7%) of the cases. Conclusion. In the Republic of Macedonia infections are the leading cause of FUO, predominately visceral leishmaniasis. In the future in patients with prolonged fever, physicians should think more often of this disease, as well as of the possibility of atypical presentation of the common classical causes of FUO.